Community Culture and Character: Correlational Study of Youth Offender in Child Prison - Dina Sukma; Azwar Ananda; Nurhizrah Gistituati; Daharnis Daharnis4 (Fakultas Ilmu Pendidikan UNP)
Youth offenders were juvenile delinquency that offend the law and according to the decision of law they must live in child prison. However, this community culture maybe has influences the development of moral character of youth offender along live in child prisoner. This study were correlational study that tries to reveal the correlation of community culture and character of youth offender by using structured questionnaire about characteristic of 20 youth offender living in jail and School Culture Scale (SCS) to measure youth offender’s perception about child prison’s community culture. Result of this study shows that there relationship between youth offender’s perception of community culture and youth offender character with Pearson correlation is 0,512 significant at 0,05. Character building will be much easier to do in an environment where there good relationship of each other, democratic, responsible, and friendly values are perceived as prevailing values.